O23-3 Does maternal exposure to air pollution from welding fumes in the work environment during pregnancy cause negative health effects in children?. (1st September 2016) - Norlén, Filip; Gustavsson, Per; Wiebert, Pernilla; Rylander, Lars; Plato, Nils; Albin, Maria; Selander, Jenny
Abstract : Background: Exposure to ambient particulate air pollution during pregnancy is associated with negative health effects in children. However, few studies have assessed the association between occupational particle exposure during pregnancy and fetal effects, especially regarding welding fumes. Aim: To investigate if occupational exposure to welding fumes is related to birth outcomes in form of small for gestational age, low birth weight or preterm birth. Methods: This retrospective cohort study was based on data from the Medical Birth Register at the National Board of Health and Welfare and includes information about all births in Sweden from 1994 to 2012 (about 1.9 million births in total). The data contains information about the mother's occupation and employment during pregnancy, outcome variables such as birth weight, small for gestational age and preterm birth of the child, and information about potential confounders such as the maternal height and weight, parity, multiple birth, smoking habits, family situation and nationality. Occupational particle exposure was assessed by a job-exposure matrix. Absence from work was assessed from information from the Swedish Social Insurance Agency. The analyses were adjusted for potential confounders and analysed with logistic regression. Results: Preliminary results on full-time working mothers with less than 30 days leave of absence, indicate a significantly increased risk for negative birth outcomes in form of small for gestational age (adjusted OR 1.37; 95% CI: 1.07–1.73), low birth weight (adjusted OR 1.56; 95% CI: 1.31–1.87) and preterm birth (adjusted OR 1.42; 95% CI: 1.22–1.65) in children to women who were exposed to welding fumes during pregnancy. Conclusions: This indicates that women should not be exposed to welding fumes during pregnancy.